Being Muslim In London Reflected In Hanif Kureishi's The Black Album Novel (1995): A Sociological Approach - Kusumawanti, Atin Jati; , Dr. Phil. Dewi Candraningrum, M.Ed; , Drs. Abdillah Nugroho, M.Hum (2013)
This study is about the life of Muslim in Being Muslim in London reflected in Hanif Kureishi's The Black Album novel by using sociological approach. It is done by establishing two objectives: the first analyzes the novel based on the structural elements of the novel and the second discribes being moeslim in London based on Sosiological Approach. This study uses qualitative research, in this method the researcher uses two data source, namely primary and secondary. Primary data source is the data of the novel, secondary data source is a sociological book and includes materials related to the study. Data collecting method in this study is library research, and in analyzing the data the researcher employs descriptive analysis. Based on the analysis, the researcher draws some conclusions as follows. First, in the novel, Hanif Kureishi shows the importance of religion in the society. Second, based on the Sociological analysis againts in social reality in the late twentieth century in England. Third, the social realities of England contribute the creation of characters and characterization, setting, plot, and theme of the story